2012
DOI: 10.1016/j.immuni.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The RIG-I-like Receptor LGP2 Controls CD8+ T Cell Survival and Fitness

Abstract: SUMMARY The RIG-I like receptors (RLRs) signal innate immune defenses upon RNA virus infection but their roles in adaptive immunity have not been clearly defined. Here we showed that the RLR LGP2 was not essential for induction of innate immune defenses, but rather was required for controlling antigen-specific CD8+ T cell survival and fitness during peripheral T cell number expansion in response to virus infection. Adoptive transfer and biochemical studies demonstrated that T cell receptor signaling induced LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 46 publications
3
111
0
Order By: Relevance
“…The central role of MAVS-dependent signaling in controlling WNV infection and pathogenesis has been established and implicates an essential role for RLRs in immunity against WNV (12,14,29,47). Herein, we delineated the role of RIG-I and MDA5 as individual PRRs in contributing to the control of WNV and induction of innate immune genes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central role of MAVS-dependent signaling in controlling WNV infection and pathogenesis has been established and implicates an essential role for RLRs in immunity against WNV (12,14,29,47). Herein, we delineated the role of RIG-I and MDA5 as individual PRRs in contributing to the control of WNV and induction of innate immune genes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…MDA5 Ϫ/Ϫ mice were kindly provided by M. Colonna (Washington University, St. Louis, MO). MAVS Ϫ/Ϫ mice were previously described (47). For production of double knockout (DKO) mice lacking both RIG-I and MDA5, RIG-I Ϫ/Ϫ and MDA5 Ϫ/Ϫ mice were intercrossed, and the resulting DKO offspring were backcrossed into a C57BL/6 background through the F3 generation.…”
Section: Mouse Studies Rig-imentioning
confidence: 99%
“…F9 embryonal carcinoma cells were obtained from ATCC and cultured as above on tissue culture plates coated with 0.1% gelatin. Dhx58 −/− mice were kindly provided by Dr. Michael Gale Jr (Suthar et al , 2012) and maintained and bred in accordance with national and institutional guidelines for animal care. Dhx58 +/+ , Dhx58 +/− and Dhx58 −/− MEFs were generated from day 13.5 embryos from Dhx58 +/− intercrosses and immortalised using a minimal dose of a retroviral vector encoding large T antigen as previously described (Schulz et al , 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Loss of LGP2 therefore leads to increased sensitivity to viruses detected by MDA5 such as picornaviridae (Venkataraman et al , 2007; Satoh et al , 2010). LGP2 may also impact RIG‐I signalling (Rothenfusser et al , 2005; Yoneyama et al , 2005), and alternative functions have been suggested by the fact that LGP2‐deficient mice have impaired CD8 + T‐cell responses to West Nile virus or lymphocytic choriomeningitis virus that appear unrelated to IFN production (Suthar et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This pathway is a subtype of pattern recognition receptors responsible for primary recognition of pathogen and host-associated molecular patterns and the subsequent activation of type I IFN production that orchestrates an innate immune response (22)(23)(24). In addition to its role in inhibiting IFNβ expression, Suthar et al recently demonstrated that LGP2 governs CD8+ T-cell fitness and survival by inhibiting death-receptor signaling (25). Here we demonstrate that suppression of LGP2 leads to an enhanced IFNβ expression and increased killing of tumor cells.…”
mentioning
confidence: 99%